Magnetic resonance elastography - McGrath, Deirdre M. (CRC Press, 2018)
Magnetic resonance elastography (MRE) is a recently developed technology that uses MRI to measure the biomechanical properties of biological tissue, such as elasticity and viscosity. Due to its sensitivity to pathology-driven alterations in tissue biomechanics, MRE is a powerful diagnostic tool for detecting and staging disease, including fibrosis, cancer and inflammation. The technology is undergoing rapid development for application to multiple organ sites in the body, and is already widely adopted in clinical practice for diagnosing hepatic fibrosis. This chapter will provide an overview of the background, methodology and clinical applications of MRE.